Effect of cadaver coatings on emergence and infectivity of the entomopathogenic nematode Heterorhabditis baujardi LPP7 (Rhabditida: Heterorhabditidae) and the removal of cadavers by ants - del Valle, Eleodoro Eduardo (2009)
Entomopathogenic nematodes (EPNs) are used for the biological control of soil insect pests worldwide and are generally applied to the soil in aqueous suspension. An alternative application method that could be especially practical and effective under certain conditions is to apply the nematode-killed insect (referred to herein as infected insect cadavers) that are placed on or in the soil and from which the nematodes emerge to seek new hosts. However, physical damage to the insect cadavers during handling and application as well as the potential detrimental impact of various soil biotic and abiotic factors could reduce the efficacy of cadaver applications. Our objective was to test the effectiveness of various protective coverings applied to Galleria mellonella insect cadavers in terms of their potential impact on the emergence and virulence of infective juveniles of the EPN Heterorhabditis baujardi LPP7, and to evaluate whether these coverings influenced cadaver removal by ants (Ectatomma spp.). The protective coveringtreatments included a commercial calcareous powder, a commercial talc powder, and gelatin capsules. The number of emerging infective juveniles (IJs) from insect cadavers formulated with talc powder (9.722 ± 1.382) and gelatin capsules (7.892 ± 1.072) was similar to the control (6.346 ± 1.311), and indicated that these coverings do not interfere with IJ emergence. However, the powdered calcareous covering significantly reduced IJ emergence. High infectivity was observed for IJs that emerged from cadavers in all treatments. Ectatomma spp. ants removed all insect cadavers from the nest entrance to a distance of 20 cm, with the exception of insect cadavers formulated in gelatin capsules, which were not removed. 2009 Elsevier Inc. All rights reserved.